STIMULUS PENINGKATAN BERAT BADAN BALITA DENGAN PEMIJATAN DAN PEMBERIAN MUFFIN PISANG - Lina Puspitasari; Ernawati Ernawati (Jurnal Inovasi Daerah, 2022)
The background of the research is that growth and development at the age of toddlers is a very important component. Considering that this is a factor supporting intelligence when entering adulthood. Weight gain is a problem that is often faced by society. Massage techniques and feeding banana muffins are an innovation that can be applied by most parents independently. The purpose of the study was to determine the effect of massage and banana muffins on the increase in toddler weight. The research method uses an experimental one group pretest posttest design. The result of the study was a greater calculated t value t table, namely (5,002 lebih dari 2,045) which means that there are benefits of toddler body massage and banana muffins to help increase toddler weight.